Dari Budaya hingga Lingkungan: Mengungkap Faktor Penentu Kinerja Pegawai Dinas PP-PA Parepare - Hudabiah, Diyah; Ali, RustanA; Darmawansah, Darmawansah; Lukman, Siti Diva Syarifah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to determine whether organizational culture and work environment partially and simultaneously affect the performance of employees of the Parepare City Women's Empowerment and Child Protection Office. The analytical method used is multiple linear regression with validity, reliability and hypothesis testing through partial tests and simultaneous tests. The results showed that organizational culture (X1) had no significant effect partially on the performance of employees of the Parepare City Women's Empowerment and Child Protection Office, this was shown based on a significant value of 0.473 greater than 0.05, the work environment (X2) had a positive and significant effect partially on the performance of employees of the Parepare City Women's Empowerment and Child Protection Office, this was shown based on a significant value of 0.000 less than 0.05. Simultaneously organizational culture and work environment affect the performance of employees of the Parepare City Office of Women's Empowerment and Child Protection, this is indicated based on a significant value of 0.000 less than 0.05.